Developing Self-Confidence through Show And Tell Techniques in Class 1 Students of UPT SD Negeri 23 Gresik - Adella Dwi Setya Wiratna; Prianggi Amelasasih (Indonesian Vocational Research Journal, 2023)
Learning in the 21st century focuses on initiatives to improve children's skills by directing the learning process, so that the learning system in the 21st century moves from initially focusing teachers on the learning process to centering students in the learning process. This requires students to be more active and confident in studying. One of the main levels of education is elementary school. However, in reality there are phenomena that show students' low self-confidence, such as 66.7% feeling embarrassed to raise their hand. Therefore, teachers try to overcome this problem, one of which is by showing and telling. This technique can be carried out in two cycles, each cycle consisting of 4 meetings. This technique can be combined with innovative things so that it is not boring, such as telling stories about favorite foods, favorite animals, and coloring. The research was conducted with 6 subjects in class 1-C students. Based on the results of research conducted by researchers at UPT SD 23 Gresik, it was found that there was an increase in the self-confidence of the students who were the subjects seen from the pre-test and post-test percentages.